EFEKTIVITAS PEMANFAATAN TEKNOLOGI PENDIDIKAN DALAM MENCIPTAKAN KUALITAS PEMBELAJARAN - Daulae, Tatta Herawati (IAIN Padangsidimpuan, 2014)
Technology is one factor supporting quality of teaching. The application of this has effectiveness. It can be seen in teaching sooner and correct to prove kind education, optimizing time teaching sharing information, and it can present material logically, scientifically and systematically.